Yoga also for the godless - Sri M (Chennai Westland, 2020)
Practitioners of the ancient science of yoga have long contended that you dont have to be a Hindu, in the conventional sense, to practise yoga, even though its origins lie in India. Renowned spiritual teacher, author, social reformer, educationist and global speaker Sri M goes a step further in this new and path-breaking book$1 (Bhe proves that, let alone belonging to a particular religion, one doesnt even need to believe in God to be a true yogi. One of the best-known Vedantic scholars of our times, he draws on his deep knowledge of ancient Indian scriptures to prove that the godless are as capable as the God-inspired of reaching the pinnacle of self-realisation and bliss through yoga. Based on a profound understanding of Patanjalis Yoga Sutras, this is a step-by-step guide to the theory and practice of yoga for those who seek to know it better, and also for the young and the millennial, who may be stepping out for the first time. In lucid prose, with photographs for visual aid, Sri M takes us through the most complex notions of breath, body and posture with admirable brevity and clarity. If you read one book on the subject of yoga, this is the one to choose..s
Keywords: Yoga